Synergistic effect of zinc-chitosan co-modified rice husk biochar on nutrient retention and controlled release of fertilizer - Pinghui Wei; Yuyang Cong; Zuwang Shao; Yang Chen; Zhongjun Liu; Zepeng Cheng; Mingfeng Wang (Bioresource Technology, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Interactions mechanisms decoding of macadamia protein isolate-procyanidins dimer complexes and synergistic effect for high internal phase Pickering emulsions stabilization - Tingting Chen; Zhipan Wang; Mingfeng Fang; Ming Zhang; Gangjun Guo; Liqing Du; Taotao Dai; Xixiang Shuai (Food Chemistry, 2026)

Electro–ultrasonic coupled for enhanced removal efficiency of toxic fine particles from biomass combustion: Performance optimization and synergistic mechanisms - Hailin Gu; Zhengcheng Lou; Mingfeng Lu; Jiaqi Ran; Xu Wang; Chengxu Tu; Guangxue Zhang; Fubing Bao (Journal of Hazardous Materials, 2026)

De novo transcriptome profiling reveals the bioeffect of the clam (Cyclina sinensis) to graded extremely low-frequency electromagnetic fields (ELF-EMF, 50 Hz) exposure - Mingming Zhang; Yuqing Fan; Mingfeng Zhu; Shouhai Liu; Hu Zhang; Chaojun Gu; Zhenyu Wang; Boping Yang; Guo Qiao (Environmental Pollution, 2026)

CFD-DEM simulations on the flow mechanisms and pressure transfer characteristics of foam-conditioned sands in a shield chamber - Daobing Zhang; Zheng Wang; Junqiu Ma; Qiujing Pan; Hao Xiong; Mingfeng Lei (Computers and Geotechnics, 2026)

Waste paper-spent coffee grounds synergistically derived carbonized cellulose aerogel for multifunctional phase change materials: Enhancing thermal energy storage, Joule/solar heating, and electromagnetic shielding - Lihang Yang; Yutao Wang; Mingfeng Chen; Dehao Li; Feng Wang; Liyuan Zhang; Yu Liang; Renjie Chen; Jun Li (Biomass and Bioenergy, 2026)

Semaglutide treatment reverses HFD induced hippocampal microglia activation and improves cognitive dysfunction - Haodong Gong; Junlu Liu; Yihan Wang; Xufan Lin; Guangsen Wu; Yichao Ou; Mingfeng Zhou; le Yang; Junxiang Peng; Xinyun Ye; Yongjia Wang; Fei Xu; et al. (Tissue and Cell, 2026)

Physics-informed neural network for predicting reaction kinetics of quinoline hydrodenitrogenation - Shihao Wang; Tao Li; Yuelin Xu; Wenbin Chen; Xiaoqian Dang; Wei Zhang; Chen Zhang; Cuiqing Li; Yong Luo; Feng Liu; Mingfeng Li (Fuel, 2026)

Probabilistic dual-dimensional seismic performance assessment of large-diameter shield tunnels considering lining–internal structure interaction - Peng Liu; Zude Ding; Mingfeng Lei; Shunguo Wang; Runtao Li (Tunnelling and Underground Space Technology, 2026)

Self-assembly of phycocyanin-nanochitin complexes for antioxidant Pickering emulsions - Yongqi Tian; Mingfeng He; Xinyi Guo; Yi Yuan; Shaoyun Wang (Food Research International, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Corrigendum to ‘Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan’ [J. Environ. Chem. Eng. 13 (6) (2025) 120190] - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2026)

Valorization of rice husk biochar as a dual-confined slow-release fertilizer: Synergistic effects of pore-throat constriction and active-site engineering - Yuyang Cong; Dongni Qiu; Jie Li; Mingfeng Wang; Donghai Wang; Zhiwen Chen; Ke Zhang (Journal of Environmental Chemical Engineering, 2026)

The adverse effects of paromomycin on early cardiovascular development in zebrafish (Danio rerio) - Yuan Lin; Yuqing Lei; Yijing Zhong; Mingfeng Cai; Zhenqi Wang; Haohang Xie; Hua Cao; Xinrui Wang (Aquatic Toxicology, 2026)

Conjunctive analysis of BSA-Seq and KASP markers unveils the preliminary candidate genes controlling chalkiness of rice grain - Mingfeng Tang; Zhongwei Wang; Tingting Zeng; Tingting Fu; Wei Zhang; Yongchuan Huang; Yanjie Yao; Yongyang Fan; Xianwei Zhang (Euphytica, 2026)

Adaptive graph learning with dynamic neural ODE for feeding intensity analysis of pearl gentian grouper in a recirculating aquaculture system - Hongpo Wang; Zeshuang Ma; Hong Zhou; Yunchen Tian; Haohui Liu; Zhanshuo Sun; Lei Jia; Jincheng Hu; Mingfeng Hu (Aquacultural Engineering, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Time-frequency simulation model of downburst wind and its effects on wind turbine responses - Qiushuang Lin; Yansong Wang; Mingfeng Huang; Kang Cai (Engineering Structures, 2026)

Probabilistic inference of wave parameters and extreme wind-wave analysis for OWTs under typhoon conditions - Shidong Liang; Mingfeng Huang; Guoqing Jia; Kang Cai; Qing Wang; Yanbo Wang (Ocean Engineering, 2026)

Pea protein-steviol glycosides complexes: Fabrication, characterization and evaluation for the emulsifying capacity - Wen Wang; Jingyu Xia; Min Zhang; Enqi Pei; Cuina Wang; Mingfeng Xu; Rongrong Yu (Food Chemistry, 2026)

GNSS/MEMS INS tightly coupled algorithm for agricultural machinery navigation enhanced by random forest-based behavioral state awareness - Yihang Feng; Guanwen Huang; Mingfeng Wang; Xin Li; Zhenhong Li; Hang Li; Kai Zhang; Ce Jing (Computers and Electronics in Agriculture, 2026)

Impacts of a layered snow density evolution scheme on Arctic snow and sea ice simulation in the CICE sea ice model - Hao Yin; Jie Su; Jiping Liu; Mingfeng Wang (Ocean Modelling, 2026)

Tuning muscovite into geopolymer product through thermal–mechanochemical activation - Weijie Chen; Guanqi Wei; Biqin Dong; Zhiwu Bie; Mingfeng Kai; Xiangping Xian; Yanshuai Wang (Journal of Cleaner Production, 2026)

Optimizing harvest aid applications for mechanical cotton harvesting: A meta-analysis of defoliation–yield trade-offs driven by crop physiology and environmental factors - Zhenwang Zhang; Yukun Wang; Xinghua Yu; Keke Yu; Huijie Hou; Qinghua Liao; Kexin Li; Zhijie Shi; Jianxin Dong; Guodong Chen; Sumei Wan; Shanwei Lou; et al. (Field Crops Research, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

A DFN–DEM approach to determine equivalent mechanical parameters of rock mass with different joint densities - Liang Wang; Shijie Zhou; Juan Huang; Mingfeng Lei; Yonggang Han; Jian Zhang; Chaojun Jia (Bulletin of Engineering Geology and the Environment, 2026)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2025)

Insight into metal-support interactions of NiMo hydrodesulfurization catalysts and their variations during application - Wenhui He; Yanjuan Xiang; Mudi Xin; Weiming Zhai; Sicong Qiao; Nan Zhang; Limei Qiu; Siyang Yan; Feng Liu; Jianqiang Wang; Guangtong Xu; Jiaxu Liu; et al. (Chemical Engineering Journal, 2025)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Exploring the Association Between Early PaCO2 Correction Speed and Cerebrovascular Autoregulation in a Porcine Model of Extracorporeal Resuscitation - Mingfeng Cao; Camila S. Contreras-Rojas; Qihong Wang; Yaman B. Ahmed; Jessica Briscoe; Carlos A. Pardo; Hannah Rando; Jin Kook Kang; Glenn Whitman; Steve Keller; Tito Porras; Sung-Min Cho (Translational Stroke Research, 2025)

A systematic review of montmorillonite-asphalt composite materials: Green clay mineral-reinforced asphalt for sustainable pavement solutions - Hao Lai; Anhua Xu; Jianliang Zhai; Youjie Zong; Wei Deng; Haoyan Guo; Bowen Guan; Mingfeng Chang; Rui Xiong; Zhenjun Wang (Applied Clay Science, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Tenebrio molitor powder enhances gelation properties of Penaeus vannamei myofibrillar protein: Mechanistic insights into structural optimization and digestibility - Mingfeng Xu; Ruixi Li; Mengting Li; Chaoyi Duan; Yinyin Wei; Xiangxiang Ni; Xiu Wang; Sida Fu; Rongrong Yu (Food Chemistry, 2025)

Influence of aromatics on the hydrodesulfurization reaction pathway of the NiMo/Al2O3 catalyst using quasi-in situ characterization techniques - Longxin Gao; Wenhui He; Weiming Zhai; Mudi Xin; Wei Wang; Yanjuan Xiang; Hui Yuan; Sa Wang; Feng Liu; Guangtong Xu; Limei Qiu; Mingfeng Li (Fuel, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Climate change induced environmental variability affects the tuna catch composition: a perspective of catch mean trophic level - Mingfeng Jiang; Jintao Wang; Xinjun Chen (Acta Oceanologica Sinica, 2025)

Isolation and structural elucidation of two novel lignans from the flowers of Gardenia jasminoides with potent α-glucosidase inhibitory activity - Qingsen Shao; Huiyu Li; Mingfeng Li; Wei Yi; Qiugui Zhou; Lijuan Zheng; Meng Wang; Hong-mei Hu; Chao Wen; Yun Tang; Wei Li (Phytochemistry Letters, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Structure-performance relationship between zeolites properties and hydrocracking performance of tetralin over NiMo/Al2O3-Y catalysts: A machine-learning-assisted study - Wei Wang; Mingfeng Li; Yang Zhang; Kang Qin; Li Zhuang; Ping Yang; Hong Nie (Fuel, 2025)

Ultrasonic assisted enzymatic extraction, structural characterization, and tyrosinase inhibition mechanism of phlorotannins from Sargassum horneri - Yongqi Tian; Ding Deng; Haitao Luo; Mingfeng He; Shaoyun Wang (Algal Research, 2025)

The local effects of new workspaces: Analyzing the relations between coworking spaces and the real estate market in Shanghai - Linrong Fu; Mingfeng Wang (Applied Geography, 2025)

Topology and element sizing optimization for performance-based design of wind sensitive tall buildings - Mingfeng Huang; Chunhe Wang; Wei Lin; Zhibin Xiao (Engineering Structures, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Cellulose-based photo-curable chiral nematic ink for direct-ink-writing 3D printing - Mingfeng Wu; Huan Wang; Afroza Akter Liza; Lukuan Guo; Wenyuan Zhu; Junlong Song; Fengshan Zhang; Yanshao Liu; Yongcan Jin; Jiaqi Guo (Carbohydrate Polymers, 2025)

Comparative study of failure mechanism of CFRP partially confined normal strength concrete (NSC) and UHPC cylinders under axial compression - Wanye Li; Yao Lu; Meizhong Wu; Peng Wang; Weiwen Li; Xingquan Wang; Mingfeng Kai; Jing Yu (Engineering Structures, 2025)

A novel geometry-informed drag term formulation for pseudo-3D Stokes simulations with varying apertures - David Krach; Felix Weinhardt; Mingfeng Wang; Martin Schneider; Holger Class; Holger Steeb (Advances in Water Resources, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

Prognostic impact of DTA mutation and co-occurring mutations in patients with myelodysplastic syndrome - Min Wang; Ping Chen; Daqi Li; Mingfeng Zhao (Molecular Biology Reports, 2024)

New insights into the remediation of chromium-contaminated industrial electroplating wastewater by an innovative nano-modified biochar derived from spent mushroom substrate: Mechanisms, batch study, stability and application - Jingyi Wang; Yongduo Guan; Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Chemosphere, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Screening of saline-alkali tolerant microorganisms and their promoting effects on rice growth under saline-alkali stress - Jiahui Fu; Yawen Liu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Journal of Cleaner Production, 2024)

Optimizing radiation capture in machine-harvested cotton: A functional-structural plant modelling approach to chemical vs. manual topping strategies - Shenghao Gu; Shuai Sun; Xuejiao Wang; Sen Wang; Mingfeng Yang; Jie Li; Paerhati Maimaiti; Wopke van der Werf; Jochem B. Evers; Lizhen Zhang (Field Crops Research, 2024)

Geochemical characteristics, Li source and genesis mechanism of thermal mineral water in Sichuan Basin, SW China - Guosen Lv; Yunhui Zhang; Jiawei Liu; Mingfeng Yang; Si Wang (Geothermics, 2024)

Scalable recovery of polyhydroxyalkanoate (PHA) from a mixed microbial culture via a novel acidification-NaClO digestion process - Yi Zhang; Yuqi Zou; Qiuyue Tao; Mingfeng Yang; Marie Harder; Han Wang; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos (Bioresource Technology Reports, 2024)

Influence of climate and land use on watershed anthropogenic phosphorus inputs and riverine phosphorus export dynamics: A global analysis - Hao Wu; Xinyi Jiao; Yucang Wang; Mingfeng Wang; Jia Zhou; Kaibin Wu; Dingjiang Chen (Science of The Total Environment, 2024)

Degradation and fermentation of hyaluronic acid by Bacteroides spp. from the human gut microbiota - Ziyi Fang; Mingfeng Ma; Yamin Wang; Wei Dai; Qingsen Shang; Guangli Yu (Carbohydrate Polymers, 2024)

Zero-valent iron (nZVI) nanoparticles mediate SlERF1 expression to enhance cadmium stress tolerance in tomato - Ali Anwar; Yudan Wang; Mengqing Chen; Shuaiwei Zhang; Jinmiao Wang; Yunqiang Feng; Yanxu Xue; Mingfeng Zhao; Wei Su; Riyuan Chen; Shiwei Song (Journal of Hazardous Materials, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

Is seasonal closure an effective way to conserve oceanic squids—Taking Chinese autonomic seasonal closure on the high seas as an example - Mingfeng Jiang; Jintao Wang; Gang Li; Bilin Liu; Xinjun Chen (Fisheries Research, 2024)

Design of active phase structure with high activity and stability in residue hydrotreating reactions - Yanzi Jia; Anpeng Hu; Dawei Hu; Mingfeng Li; Huifeng Li; Qinghe Yang; Zhiwei Liu; Zhicai Shao; Shuangqin Zeng; Xinqiang Zhao; Yifan Wang (Fuel, 2024)

Probabilistic evaluation for excavation-induced longitudinal responses of existing shield tunnel in spatially random soils - Zuxian Wang; Chenghua Shi; Haiyong Chen; Mingfeng Lei (Computers and Geotechnics, 2024)

Separation of spring viraemia of carp virus from large-volume samples using immunomagnetic beads - Jing Hongli; Zhang Min; Gao Longying; Si Liegang; Wang Na; Ge Mingfeng; Xu Shengwei; Wang Jianping; Wu Shaoqiang (Archives of Virology, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

Evaluation of three prevalent global riverine nutrient transport models - Xinyi Jiao; Jia Zhou; Minpeng Hu; Mingfeng Wang; Hao Wu; Kaibin Wu; Dingjiang Chen (Environmental Science and Pollution Research, 2023)

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

Insight into the effect of microplastics on the adsorption and degradation behavior of thiamethoxam in agricultural soils - Mingfeng Hu; Lulu Huang; Ya Wang; Huihua Tan; Xiangyang Yu (Chemosphere, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

A novel approach to achieving more efficient production of the mature form of human IL-37 in plants - Yao Zhang; Nadiyah Alqazlan; Zihe Meng; Jingyao Zhao; Nan Liu; Yuxin Zhang; Mingfeng Feng; Shengwu Ma; Aoxue Wang (Transgenic Research, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Effects of the skirt length and embedment depth on the capacity of a skirted spudcan foundation under combined loading - Shuai Yin; Zhen Wang; YuZhou Xiang; ShiJie Xu; MingFeng Cheng; WenChang Yan; GuoJun Cai; JiangTao Yi (Ocean Engineering, 2023)

Soil nitrification process played a key role in alleviating continuous cropping limitation induced by fumigation - Jing Xiong; Yongjun Liu; Tianbo Liu; Shuguang Peng; Mingfeng Cao; Zhenhua Wang; Lei Zhou; Junliang Zou; Zhenghua Liu; Jixiang Ai; Yabing Gu; Huaqun Yin; et al. (Plant and Soil, 2023)

Seasonal pollution and surface characteristics of microplastics in surface water in the Wanzhou section of the Three Gorges Reservoir, China - Ying He; Qian Huang; Qilong Wang; Mingfeng Tang; Xiaoyu Lu; Fei Cheng; Guosheng Xiao (Environmental Science and Pollution Research, 2023)
The pollution of freshwater environments with microplastics (MPs) has attracted increasing attention owing to their threats to aquatic ecosystems and human health. Here, we sampled and analyzed MPs from mainstream, tributary, and backwater areas in the Wanzhou section of the Three Gorges Reservoir (TGR) in impoundment and flood periods. Microplastic pollution was the most severe in the backwater areas. The average abundance of MPs reached the highest value in the flood period (5.27±3.47×10 7 items km −2 ), which was 3–5 times that in the impoundment period. In the 0.3–5 mm size class, the 1–5 mm fraction was the most abundant, accounting for more than 81% in the flood period and 68% of the total MP particle abundance in the impoundment period in the mainstream and backwater areas. However, 0.3–1 mm MPs contributed more than 50% in the tributaries during the impoundment period. Polystyrene, polypropylene, and polyethylene MPs were detected in foam, fragment, sheet, and line-shaped MP particles. White, opaque, foamed polystyrene MPs contributed 32–81% to total MP particle abundance in the watershed. Microplastic particle surfaces showed signs of damage and oxidation, and ten different elements were found. Oxygen was clustered on the surface of foam and fragment MPs. Microplastic pollution was severe in the Wanzhou watershed. Especially in the backwater areas, oxidized MPs of variable shapes derived mainly from surface runoff in the flood period and sewage discharge in the impoundment period were abundant. The results of this study contribute to understanding seasonal pollution patterns and surface characteristics of MPs in the TGR and similar watersheds.

Nitrogen Application Promotes Drought-Stressed Sugar Beet Growth by Improving Photosynthesis, Osmoregulation, and Antioxidant Defense - Hongliang Zhou; Pengjie Xu; Lijuan Zhang; Ruimin Huang; Mingfeng Yang; Kaiyong Wang; Hua Fan (Journal of Soil Science and Plant Nutrition, 2023)

Spatiotemporal distribution of dust aerosol optical properties from CALIPSO and CATS observations in Xinjiang, China - Gang Ren; Baiwan Pan; Jin Wang; Dongliang An; Mingfeng Yang; Hui Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Precursors and formation pathways of furfural in sugarcane juice during thermal treatment - Huimei Huang; Jiebo Chen; Mingfeng Zheng; Lulu Zhang; Hongfei Ji; Huajin Cao; Fengxia Dai; Lu Wang (Food Chemistry, 2023)

The genesis of the Ni–Cu sulfide mineralization of the carboniferous Haibaotan intrusion, Eastern Tianshan, Central Asian Orogenic Belt - Mingfeng Qiu; Yun Zhao; Chunji Xue; Jia Chen; Xiaoping Ma; Lu Wang; Liang Yu; Yanxiang You (International Journal of Earth Sciences, 2023)

Improved analytical solution for ground movements induced by circular tunnel excavation based on ground loss correction - Binbin Zhu; Peng Zhang; Mingfeng Lei; Lichuan Wang; Lun Gong; Chenjie Gong; Fudong Chen (Tunnelling and Underground Space Technology, 2023)

SERS “hot spot” enhance-array assay for misfolded SOD1 correlated with white matter lesions and aging - Feng Gao; Jingyi Sun; Minmin Yao; Yanan Song; Hui Yi; Mingfeng Yang; Qingbin Ni; Jiming Kong; Hui Yuan; Baoliang Sun; Ying Wang (Analytica Chimica Acta, 2023)

Behaviour of electroosmotic consolidation by electrode configuration and fracture grouting - Yunguo Du; Chao Zhang; Changfei Gou; Wenwen Wu; Xiaobing Li; Xiuqing Hu; Wang Chaoliang; Li Mingfeng (Marine Georesources & Geotechnology, 2022)

Effect of initial deviatoric stress on anisotropy of marine clay during principal stress rotation - Heng Zhuang; Xiuqing Hu; Lin Guo; Li Mingfeng; Wang Chaoliang; Hongke Du; Jingqiang Jin (Marine Georesources & Geotechnology, 2022)

Oceanic vertical mixing of the lower halocline water in the Chukchi Borderland and Mendeleyev Ridge - Long Lin; Hailun He; Yong Cao; Tao Li; Yilin Liu; Mingfeng Wang (Acta Oceanologica Sinica, 2021)

The effects of initial deviatoric stress on anisotropy of marine clay and strain components - Heng Zhuang; Mingfeng Li; Chaoliang Wang; Lin Guo; Dikang Zhang; Hongke Du; Yunguo Du (Marine Georesources & Geotechnology, 2021)

Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading - Dikang Zhang; Hongtao Fu; Jun Wang; Dongqi Zhu; Xiuqing Hu; Yunguo Du; Changfei Gou; Chaoliang Wang; Mingfeng Li; Hai Wu (Marine Georesources & Geotechnology, 2021)

Carbonyl Reductase 1 Attenuates Ischemic Brain Injury by Reducing Oxidative Stress and Neuroinflammation - Leilei Mao; Kun Wang; Pengjie Zhang; Shihao Ren; Jingyi Sun; Mingfeng Yang; Feng Zhang; Baoliang Sun (Translational Stroke Research, 2021)

Anisotropic properties of shale and its impact on underground structures: an experimental and numerical simulation - Chaojun Jia; Qiang Zhang; Mingfeng Lei; Yanni Zheng; Juan Huang; Lichuan Wang (Bulletin of Engineering Geology and the Environment, 2021)

CYP2C9 inhibits the invasion and migration of esophageal squamous cell carcinoma via downregulation of HDAC - Zhenzhen Jiang; Xiaoli Zheng; Weijia Wang; Liqing Qiu; Lingrong Yang; Mingfeng Jiang; Yuhui Hua (Molecular and Cellular Biochemistry, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Improved robust tensor principal component analysis for accelerating dynamic MR imaging reconstruction - Mingfeng Jiang; Qiannan Shen; Yang Li; Xiaocheng Yang; Jucheng Zhang; Yaming Wang; Ling Xia (Medical & Biological Engineering & Computing, 2020)

Debris flows originating from colluvium deposits in hollow regions during a heavy storm process in Taining, southeastern China - Yong Zhang; Ningsheng Chen; Mei Liu; Tao Wang; Mingfeng Deng; Kanglin Wu; Binish Raj Khanal (Landslides, 2020)

Design, synthesis, and SAR study of highly potent, selective, irreversible covalent JAK3 inhibitors - Linhong He; Mingfeng Shao; Taijin Wang; Tingxuan Lan; Chufeng Zhang; Lijuan Chen (Molecular Diversity, 2018)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Advanced glycation end products promote proliferation and suppress autophagy via reduction of Cathepsin D in rat vascular smooth muscle cells - Mingfeng Ma; Xiaofan Guo; Ye Chang; Chao Li; Xin Meng; Si Li; Zhen-Xian Du; Hua-Qin Wang; Yingxian Sun (Molecular and Cellular Biochemistry, 2015)

Sec Pathway Influences the Growth of Deinococcus radiodurans - Liangyan Wang; Hongmei Tan; Kaiying Cheng; Mingfeng Li; Xin Xu; Jing Wang; Yuejin Hua (Current Microbiology, 2015)

Pyruvate decarboxylase and alcohol dehydrogenase overexpression in Escherichia coli resulted in high ethanol production and rewired metabolic enzyme networks - Mingfeng Yang; Xuefeng Li; Chunya Bu; Hui Wang; Guanglu Shi; Xiushan Yang; Yong Hu; Xiaoqin Wang (World Journal of Microbiology and Biotechnology, 2014)

Serpentinization, abiogenic organic compounds, and deep life - XianBin Wang; ZiYuan Ouyang; ShengGuang Zhuo; MingFeng Zhang; GuoDong Zheng; YongLi Wang (Science China Earth Sciences, 2014)

Obesity-related genetic variants, human pigmentation, and risk of melanoma - Xin Li; Liming Liang; Mingfeng Zhang; Fengju Song; Hongmei Nan; Li-E Wang; Qingyi Wei; Jeffrey E. Lee; Christopher I. Amos; Abrar A. Qureshi; Jiali Han (Human Genetics, 2013)

Interfering growth of malignant melanoma with Ang2-siRNA - Biao Wang; Zhaoliang Liu; Mingfeng Zhang; Xiuying San; Yanding Zhang; Weiqiang Zhang; Meishui Wang (Molecular Biology Reports, 2013)

Three nth homologs are all required for efficient repair of spontaneous DNA damage in Deinococcus radiodurans - Xiaoting Hua; Xin Xu; Mingfeng Li; Chao Wang; Bing Tian; Yuejin Hua (Extremophiles, 2012)

Expression of SHH signaling pathway components in the developing human lung - Mingfeng Zhang; Hong Wang; Hongqi Teng; Jueping Shi; Yanding Zhang (Histochemistry and Cell Biology, 2010)